Mapping lithology and hydrothermal alteration in geothermal systems using portable X-ray fluorescence (pXRF): A case study from the Tauhara geothermal system, Taupo Volcanic Zone. (November 2016) - Mauriohooho, Kate; Barker, Shaun L.L.; Rae, Andrew
Highlights: 304 geothermal drill cuttings were analysed by portable x-ray fluorescence (pXRF). PXRF results are accurate for elements with an atomic number over 17. Immobile elements (Y, Zr) define formation boundaries and identify sub-units. Mobile elements (Rb, Ba, Ca, K) correlate with known areas of fluid flow. PXRF should be used while drilling to improve geological models in real time. Abstract: Portable x-ray fluorescence (pXRF) analyzers are widely used in the environmental and mineral exploration fields. pXRF analyzers can rapidly and inexpensively provide chemical concentrations on a variety of elements, often with detection limits of ∼1–5 ppm. We compared portable XRF results from untreated geothermal drill cuttings with laboratory XRF results from pressed pellet and lithium borate fused beads prepared from powders crushed from the same samples. It is demonstrated that the portable XRF results are accurate for many elements, particularly for those with atomic numbers greater than 17. 304 cutting samples from three drillholes in the Tauhara geothermal field were subsequently analyzed by pXRF. Downhole elemental concentrations plotted against lithological units defined on geological well logs indicate that significant variations in elemental concentrations occur, some of which correlate with logged lithology boundaries. Other chemical variations appear to define previously unrecognized subunits, as well as areas of hydrothermal alteration. We suggest that pXRF should become a routine part of the characterization of geothermal cuttings during geothermal exploration and well drilling, as the chemical results are accurate, rapid and inexpensive, and the results can be used to define lithological boundaries and potentially correlate between drillholes, therefore improving geologic, stratigraphic and hydrothermal alteration models of the geothermal field.